2015
DOI: 10.1002/2014gl062891
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of gravity wave activity at midlatitudes from 7 years of COSMIC GPS and Rayleigh lidar temperature observations

Abstract: Seven year series of gravity wave (GW) potential energy at midlatitude stratosphere (10 to 50 km) is constructed by combining temperature profiles provided by Constellation Observing System for Meteorology, Ionosphere and Climate (COSMIC) GPS satellite constellation and Rayleigh lidar operating at Haute Provence observatory in Southern France. The combined series are used to evaluate the representation of GW in Modern Era Retrospective-Analysis for Research and Applications reanalysis. The seasonal and zonal v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 49 publications
1
32
0
Order By: Relevance
“…They are, however, rarely observed and do not influence the estimates of statistical moments. Tsuda et al (2000), de la Torre et al (2006), and Khaykin et al (2015) (further references can be found in these papers) studied the global morphology of E p in the stratosphere using σ 2 δT /T evaluated from temperature profiles retrieved from GPS/MET data. The wave activity can be monitored directly from measurements of amplitude and phase fluctuations of RO signals, using the simple relationships that link them to IGW parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are, however, rarely observed and do not influence the estimates of statistical moments. Tsuda et al (2000), de la Torre et al (2006), and Khaykin et al (2015) (further references can be found in these papers) studied the global morphology of E p in the stratosphere using σ 2 δT /T evaluated from temperature profiles retrieved from GPS/MET data. The wave activity can be monitored directly from measurements of amplitude and phase fluctuations of RO signals, using the simple relationships that link them to IGW parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, an increasing number of papers discuss the use of GPS for the study of atmospheric inhomogeneities. Some papers link the fluctuations of the amplitude and the phase of radio signals in the stratosphere to IGWs (Tsuda et al, 2000;Steiner and Kirchengast, 2000;Wang and Alexander, 2010;Khaykin et al, 2015), while other papers attribute this part to isotropic turbulence in the lower stratosphere and troposphere (Cornman et al, 2004(Cornman et al, , 2012Shume and Ao, 2016). Therefore, it is necessary to formulate clear criteria for determining what type of inhomogeneities, isotropic or anisotropic, dominate radio signal fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…The threshold DIV values of ± 2•10 -4 s -1 are chosen as suggested by Dörnbrack et al (2012) and as used by Khaykin et al (2015) to locate hot spots of stratospheric gravity wave activity. In contrast to the V H IGW -field, the horizontal divergence is not spectrally filtered and contains contributions from all resolved wavenumbers.…”
Section: Inertia-gravity Wavesmentioning
confidence: 99%
“…Most of the existing studies concentrate on statistical aspects derived from high-vertical resolution radiosondes (e.g., Yoshiki and Sato, 2000;Yoshiki et al, 2004), from ground-based (e.g., Whiteway et al, 1997, Whiteway and Duck, 1999, Khaykin et al, 2015 and space-borne (e.g., Waters, 1996, Hindley et al, 2015) remote-sensing observations. The observations of Whiteway 15 at Eureka, Nunavut, Canada (80°N) during four Arctic winters showed an increase of stratospheric gravity wave energy in the vicinity of the PNJ.…”
Section: Introductionmentioning
confidence: 99%
“…There are specific case studies, e.g., [1][2][3][4][5][6][7]; there are climatologies to determine the seasonal dependence of gravity wave activity or their relation to the atmospheric background conditions [8][9][10][11][12][13][14][15][16][17][18][19]; and there are studies developing the methodology to retrieve gravity wave signatures, e.g., [20]. Recently, the output of the high-resolution analyses of the Integrated Forecast System of the ECMWF was compared with lidar measurements in the middle atmosphere, e.g., [21].…”
Section: Introductionmentioning
confidence: 99%